RESULTS OF MORPHOLOGICAL, TEMPORAL AND SPECTRAL ANALYSIS OF ARTERIAL OSCILLOGRAMS OF PATIENTS WITH DIABETES MELLITUS - Vakulenko, D. V.; Vakulenko, L. O.; Kutakova, O. V.; Lesiv, V. V. (Medical Informatics and Engineering, 2018)
The morphological, temporal, and spectral analysis of arterial oscillograms has shown that patients with diabetes mellitus have an inherent disruption of the vegetative nervous system activity (a significant increase of sympathetic part activity with a negligible increase of parasympathetic part activity); reduction of vascular wall excitability during cuff arm compression, disturbance of coordination in local self-regulating mechanisms and central neurohumoral regulation of cardiovascular system activity, decrease of vasomotor centre activity and elastic properties of the vascular wall. Oscillograms indicators AMo, IN, IVR, BP, RMSSD depend on the elastic properties of the vascular wall. The use of morphological, temporal and spectral analysis of arterial oscillograms in patients with diabetes mellitus will help physician more effectively plan a preventive, diagnostic, and therapeutic process.